THE CONTROLLED CHOKE TRANSFORMER IN THE STRUCTURE OF THE ELECTROMECHANICAL SYSTEM FOR GENERATING ALTERNATING CURRENT OF FIXED FREQUENCY - S. V. Mishin (Научный вестник МГТУ ГА, 2016)
This article briefly describes the design of controlled choke transformer regulator. The electrical circuit and the results of laboratory tests in the form of characteristics of idling, short circuit and performance are presented. The expediency of application of such devices in the electromechanical system of generating alternating current of constant frequency is grounded.